Praktik Community Relations dalam Membangun Hubungan dan Advokasi Merek pada Komunitas Somethinc Town - Cecilia Grafiani; Raveena Alifia Sahara (Jurnal InterAct, 2025)
This study aims to analyze the role of community relations practices implemented by Somethinc through its digital community called Somethinc Town, in building relationships between the brand and consumers and in contributing to the formation of brand advocacy. The research employed a descriptive qualitative approach, with data collected through in-depth interviews, digital observation, and documentation of community activities. The data was analysed using the framework of Relationship Management Theory (RMT), which emphasizes five relational dimensions: trust, openness, involvement, commitment, and control mutuality. The findings show that Somethinc Town functions not merely as a communication or product promotion channel, but as a relational space that facilitates social interactions, shared experiences, and collective values. Community relations practices carried out through various online and offline activities encourage participatory two-way communication, enabling community members to move beyond passive message recipients to become actively involved in discussions, community activities, and brand development processes. The relational bonds formed through the five dimensions of RMT generate a level of support that exceeds brand loyalty, manifesting as brand advocacy. This is reflected in community members’ voluntary willingness to defend, recommend, and promote Somethinc products without financial incentives, as well as their contributions to public education regarding cosmetic safety and industry ethics. The study contributes theoretically by reinforcing the relevance of Relationship Management Theory in understanding digital consumer communities, and practically by offering guidance for local brands in designing authentic, participatory, and sustainable relationship strategies within Indonesia’s beauty industry.